1980
DOI: 10.1037/0021-843x.89.5.662
|View full text |Cite
|
Sign up to set email alerts
|

Causal perceptions of stressful events in depressed and nondepressed outpatients.

Abstract: Recent attributional formulations of depression have not typically been tested in clinical populations, and the studies that have been reported commonly employ contrived failure tasks. In the present study cognitions about the causes and consequences of recent personally stressful life events were examined in depressed and nondepressed outpatients. Depressed persons were found to characterize the cause of their most upsetting events as internal, intended, global, expected, and stable; however, no overall diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 10 publications
1
67
0
Order By: Relevance
“…Based on previous studies (Abramson et al, 1977(Abramson et al, , 1978Harvey et al, 1978;Gong-Guy et al, 1980), depression attribution in negative events plays a key role in DPs. To examine the different attribution bias in negative life events, we separately examine the effects of each condition for two groups.…”
Section: Statistical Image Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…Based on previous studies (Abramson et al, 1977(Abramson et al, , 1978Harvey et al, 1978;Gong-Guy et al, 1980), depression attribution in negative events plays a key role in DPs. To examine the different attribution bias in negative life events, we separately examine the effects of each condition for two groups.…”
Section: Statistical Image Analysismentioning
confidence: 97%
“…Generally, healthy people usually display a so-called ''self-serving'' bias: the propensity to attribute success to the self and failure to external factors (Miller and Ross, 1975). Nevertheless, a number of theorists have further suggested that depressive symptoms might be profitably understood by taking into account the causal attributions for the bad events in their lives (Abramson and Sackheim, 1977;Abramson et al, 1978;Golin et al, 1981;Gong-Guy and Hammen, 1980;Harvey, 1981;Harvey et al, 1978).…”
Section: Introductionmentioning
confidence: 92%
“…Depressed clients are more likely to attribute negative life events to internal, global, and stable causes (Gong-Guy & Hammen, 1980). Furthermore, depressed clients tend to view stressful events as distressing and requiring substantial life change (Robins, Block, & Peselow, 1990).…”
Section: Retain a Positive Attitudementioning
confidence: 99%
“…Recently several self-report instruments have been developed to assess attribution style (Gong-Guy & Hammen, 1981;Peterson, Semrnel, Baeyer, Abramson, Metalsky, & Seligman, 1982;Russel, 1982;Girodo, Dotzenroth, & Stein, 1981) either to measure causal attributions on hypothetical-or on real life-events and by that means test the hypothesis of learned helplessness. Apart from the 'traditional' attributional dimensions several authors elaborated the model using other cognitive variables as chance, intention, and expectation (Gong-Guy & Hammen, 1980). Several observations can be made about the existing literature.…”
mentioning
confidence: 99%